A Novel Method for Determining Geophone Orientations From Zero-Offset VSP Data Constrained by Scalar Field - Yang, Yuyong; Qi, Qiaomu; Zhou, Huailai; Wang, Zhengyang (Frontiers in Earth Science, 2022)
In vertical seismic profile (VSP) acquisition, the orientation of the three-component geophones in a borehole is often not aligned due to the random rotation of the wireline receiver array. Knowing the geophone orientation is crucial for rotating the waveforms back to the position where the geophones are assumed to be aligned. This procedure is critical in three-component VSP data processing as it provides the correct wavefields for subsequent VSP data imaging and inversion. For zero-offset or near zero-offset VSP measurements, the direct P-wave propagates nearly vertically, the horizontal geophones receive only a small fraction of the direct P-wave energy. The first-arrival in the horizontal component data is often of low signal-to-noise ratio (SNR). As a result, it is difficult to apply conventional first-arrival-based methods for obtaining accurate geophone orientations. On the other hand, a seismic event composed of individual waveform would achieve maximum correlation if all corresponding geophones are aligned. The geometric characteristics, i.e., the slope and continuity of a seismic event in the vector wavefield are the same with those of the modules of vector wavefield. The latter also known as the scalar wavefield can be used for scanning geophone orientations based on waveform correlation. In this study, we propose to use the scalar field to extract the slope of seismic events. With the constraint of the slope, we calculate the orientation of the individual geophone. We use both synthetic and field data to demonstrate the effectiveness and applicability of the proposed method. The results show that the new method can provide wavefields of horizontal component VSP data with much higher accuracy and resolution.